3D Hybrids of Interconnected Porous Carbon Nanosheets/Vertically Aligned Polyaniline Nanowires for High‐Performance Supercapacitors. Issue 11 (13th March 2018) - Zhang, Wang; Jin, Xuanzhen; Chai, Hua; Diao, Guowang; Piao, Yuanzhe
Abstract: 3D hybrids of interconnected porous carbon (PC) nanosheets/vertically aligned polyaniline (Pani) nanowires are prepared by a cost‐effective facile approach and used as high‐performance supercapacitor electrodes. The 3D PC/Pani hybrids are obtained by a simple in situ growth of Pani on 3D PC with a high specific surface area and good electrochemical performance fabricated via a one‐step thermal pyrolysis of potassium citrate. The 3D PC/Pani hybrids show an excellent specific capacitance of 512 F g −1 at 1 A g −1 in the three‐electrode configuration, which is attributed to the synergistic effect of PC and Pani in the composite. In addition, the as‐assembled asymmetric supercapacitor of PC/Pani composites exhibits good capacitive properties and a long‐term cycling stability of 91% after 3000 cycles at 5 A g −1 . Owing to its cost‐effective preparation and high electrochemical performance, the PC/Pani hybrid composite has significant potential for use as practical electrode materials of supercapacitors. Abstract : 3D hybrids of interconnected porous carbon nanosheets/vertically aligned polyaniline nanowires are prepared by a cost‐effective facile approach and used as high‐performance supercapacitor electrodes.